Do Digital Adaptation, Energy Transition, Export Diversification, and Income Inequality Accelerate towards Load Capacity Factors across the Globe? - Masahina Sarabdeen; Manal Elhaj; Hind Alofaysan (Energies, 2024)
To limit global warming to 1.5 °C, it is imperative to accelerate the global energy transition. This transition is crucial for solving the climate issue and building a more sustainable future. Therefore, within the loaded capacity curve (LCC) theory framework, this study investigates the effects of digital adaptation, energy transition, export diversification, and income inequality on the load capacity factor (LCF). This study also attempts to investigate the integration effects of digital adaptation and energy transition, and digital adaptation and export diversification, on LCF. Furthermore, we explored how income inequality influences the LCF in economies. For this study, 112 countries were selected based on the data availability. Panel data from 2010 to 2021 were analyzed using the STATA software 13 application utilizing a two-step system generalized method of moments (GMM) approach. First, interestingly, our finding shows that digital adaptation and income significantly affect the LCF. An increase in income increases the LCF among the middle-income group of countries. Therefore, LCC is confirmed in this research. Surprisingly, energy transition, export diversification, and foreign direct investment negatively impact the LCF in the base model. Second, the impact of integrating digital adaptation and energy transition has a positive effect on LCF. Third, a negative correlation was observed between the interaction of export diversification and digital adaptation with the LCF. Fourth, a positive correlation was observed between the interaction of renewable energy and digital adaptation with the LCF. Finally, this study explores the impact of the energy transition, export diversification, and income inequality on the LCF with reference to the Organization of Petroleum Exporting Countries (OPEC). The result shows a negative effect between export diversification and LCF among OPECs at a 10% significance level. To improve the quality of our planet, policymakers must understand the forces causing climate change. By adopting a comprehensive perspective, the study aims to understand how these interrelated factors collaboratively influence the LCF thoroughly. Additionally, this research seeks to provide valuable insights related to energy transition, digital adaptation, and export diversification to policymakers, researchers, and stakeholders regarding possible avenues for cultivating a more joyful and sustainable global community.